Astragalin-functionalized ultrasmall nanoparticles modulate the complement pathway to inhibit microglial synaptic phagocytosis for reducing anesthetic neurotoxicity - Gang Wang; Yaobao Han; Ke Peng; Zhilin Jiang; Tingting Wang; Qing Zheng; Wenting Li; Hanbing Xu; Fuhai Ji; Zhen Li (Materials Today Bio)
Synaptic impairment is identified as a primary pathology in sevoflurane-induced neurotoxicity, contributing to neurobehavioral and neurodevelopmental deficits. Synaptic loss in neurons occurs through microglia-mediated synaptic phagocytosis via the complement pathway. Astragalin, a natural flavonoid compound, exhibits diverse bioactivities, such as anti-tumor, anti-complement, and anti-inflammatory effects. Herein, astragalin-functionalized Cu2-xSe nanoparticles (CSPA NPs) can effectively inhibit the complement pathway, mitigating microglia-mediated synaptic phagocytosis and promoting synaptic restoration to repair sevoflurane-induced neurotoxicity. They efficiently target and reduce microglial activation and phagocytosis. By downregulating sortilin, CSPA NPs increase progranulin expression, promoting TFEB cytoplasmic translocation to decrease lysosomal activity and microglial phagocytosis. Furthermore, CSPA NPs decrease complement C1q and C3 levels, inhibiting microglial synaptic engulfment and ameliorating cognition dysfunction in sevoflurane-treated mice. This study illustrates that CSPA NPs inhibit microglial synaptic elimination via the complement pathway, alleviating sevoflurane-induced neurotoxicity and providing insights into treating complement pathway-related diseases.